Measuring bone defects for acetabular revision surgery for choosing an appropriate reconstruction strategy: A concept study on plastic models. (August 2019) - Dankl, Lukas; Mayr, Agnes; Kaufmann, Gerhard; Thaler, Martin; Nogler, Michael; Putzer, David
Abstract: Background: Bone defects can be filled with autografts, allografts and artificial bone-materials. The aim of this study was to evaluate whether the digitization of known defect models with a navigation system is a reliable measurement method for estimating the size of a bone defect. Methods: Six preformed, cylindrical and cone-shaped defects on an artificial hip-bone were digitalized by six different observers. Reference volumes were gathered by measuring the depth of the defects, using an alginate impression material to fill out the defects and calculating the volumes from a CT scan. Results: One out of the six preformed defects showed a statistically significant difference between the digitalization and the calculation, four showed a significant difference between the digitalization and the mould as well as between the digitalization and the CT calculation. Conclusions: This technique offers satisfactory results and consistent reproducibility when digitalizing big defects with relatively simple shape. Decreasing size and increasing complexity of the defects leads to more imprecise measurements. Highlights: Digitalization of bone defects is possible using navigation systems. This technique shows good results and reproducibility when measuring big defects. The known size of a defect can be used to determine further treatment.